(untitled) (Journal of Face Aesthetics, 2019)
Actinic keratosis (AK) is a common disorder, presented with scaly, erythematous lesions associated with chronic exposure to ultraviolet (UV) radiation and possible transforming into an invasive squamous cell carcinoma. Photodynamic Therapy (PDT) is one of non-invasive methods of treatment AK. We report the case of a 61-year-old female patient with AK treated with PDT in whom erythema and pustules with concomitant elevated body temperature were observed, what might indicate on reactivation of herpes simplex virus (HSV) infection.